2006
DOI: 10.1016/j.ejcts.2006.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Flow dynamics and wall shear stress in the left internal thoracic artery: composite arterial graft versus single graft☆

Abstract: The LITA shows a marked adaptability to flow dynamics. The proximal tract of the LITA in Y-group is able to match increased flow requirements, probably through the release of endothelial vasoactive mediators. Flow velocity spectra acquired in the proximal LITA in Y-group resemble the biphasic coronary artery pattern with a clear diastolic predominance. This pattern is probably consequence of the increase of blood flow due to the lower vascular resistance of the Y-graft system and to the active dilatation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 13 publications
2
6
0
1
Order By: Relevance
“…
Through their recent article, Lemma et al [1] reported gratifying adaptability to the flow of proximal LIMA when using Y-graft revascularisation, corroborating previous investigation in this field [2], and on which the authors should be congratulated.Although the authors concluded that the distal flow of LIMA is similar between Y-graft and single graft groups, exclusive Ygraft revascularisation may raise concerns over attendant physiological disturbances afflicted to the integrated perfusion of coronary systems and their interplay. Apart from successfully measuring the relative flow and demonstrating technical feasibility, the exclusive T-or Y-graft nonetheless results in a perfusion pattern similar to a left-dominant coronary system.

It is well documented that the systolic antegrade flow of LAD is composed by antegrade flow from left Valsalva sinus and systolic retrograde given way by its collaterals such as septal and diagonal arteries [3].

…”
supporting
confidence: 58%
See 1 more Smart Citation
“…
Through their recent article, Lemma et al [1] reported gratifying adaptability to the flow of proximal LIMA when using Y-graft revascularisation, corroborating previous investigation in this field [2], and on which the authors should be congratulated.Although the authors concluded that the distal flow of LIMA is similar between Y-graft and single graft groups, exclusive Ygraft revascularisation may raise concerns over attendant physiological disturbances afflicted to the integrated perfusion of coronary systems and their interplay. Apart from successfully measuring the relative flow and demonstrating technical feasibility, the exclusive T-or Y-graft nonetheless results in a perfusion pattern similar to a left-dominant coronary system.

It is well documented that the systolic antegrade flow of LAD is composed by antegrade flow from left Valsalva sinus and systolic retrograde given way by its collaterals such as septal and diagonal arteries [3].

…”
supporting
confidence: 58%
“…Through their recent article, Lemma et al [1] reported gratifying adaptability to the flow of proximal LIMA when using Y-graft revascularisation, corroborating previous investigation in this field [2], and on which the authors should be congratulated.…”
supporting
confidence: 58%
“…From the anesthetized in vivo hemodynamic measurements, carotid artery wall shear stress (WSS) was calculated as previously reported [25]:…”
Section: Methodsmentioning
confidence: 99%
“…Apart from such peculiar conditions, detractors of the composite arterial grafting raised doubts about the flow adaptability of the left IMA when used as the only inflow for composite arterial grafting. Nevertheless, there is ample evidence from several studies published in the past decade [29][30][31][32][33] that the left internal thoracic artery (LITA) shows a marked adaptability to flow dynamics. In particular, an elegant study by Affleck and colleagues [30] identified a consistent flow reserve in the LIMA-radial composite grafting, as demonstrated by their intraoperative flow recordings for each limb of the T graft before and after distal anastomoses in 204 patients.…”
Section: Concerns and Controversiesmentioning
confidence: 99%